2017
DOI: 10.5194/acp-2017-149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the spatio-temporal representativeness of observations

Abstract: The discontinuous spatio-temporal sampling of observations has an impact when using them to construct climatologies or evaluate models. Here we provide estimates of this so-called representation error for a range of timescales and length scales (semi-annually down to sub-daily, 300 to 50 km) and show that even after substantial averaging of data significant representation errors may remain, larger than typical measurement errors. Our study considers a variety of observations: ground-site or in situ remote sens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…To be able to evaluate and intercompare the remote sensing datasets, they will need to be collocated in time and space to reduce representation errors (Colarco et al, 2014;Schutgens et al, 2016bSchutgens et al, , 2017. This is achieved by only retaining data from multiple datasets if they occur within the same spatio-temporal window.…”
Section: Collocation and Analysis Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…To be able to evaluate and intercompare the remote sensing datasets, they will need to be collocated in time and space to reduce representation errors (Colarco et al, 2014;Schutgens et al, 2016bSchutgens et al, , 2017. This is achieved by only retaining data from multiple datasets if they occur within the same spatio-temporal window.…”
Section: Collocation and Analysis Methodologymentioning
confidence: 99%
“…Intriguingly, the highest product correlations and lowest RMS differences with AERONET are found for a collocation requirement of 3 hours and at least 5 AERONET measurements and not for a tighter constraint of 1 hour. In Schutgens et al (2017) it was shown that point measurements become more spatially representative for a larger area by temporal averaging. It was estimated that a 1 o grid-box was best represented by a point observation if its measurements were averaged over 4 hours.…”
Section: Selection Of Aeronet Sites and Collocation Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly large biases can occur when care is not taken to ensure temporal synchronicity in data [125]. Furthermore, a lack of consideration of the diurnally biased sampling associated with polar-orbiting satellites can bias results significantly [93,123]. The spatial heterogeneity of observations also needs careful consideration.…”
Section: Ensuring Scale Awareness In Model-observation Intercomparisonsmentioning
confidence: 99%
“…The spatial heterogeneity of observations also needs careful consideration. Data is often discontinuous in space and time, requiring geospatial statistical methods to address data heterogeneity when comparing to regularly gridded model output [123].…”
Section: Ensuring Scale Awareness In Model-observation Intercomparisonsmentioning
confidence: 99%